2020
DOI: 10.3390/f11101098
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering the Contributions of Forests and Trees to Transition Global Food Systems

Abstract: The importance of forests to safeguard agricultural production through regulating ecosystem services such as clean water, soil protection, and climate regulation is well documented, yet the contributions of forests and trees to provide food for the nutritional needs of the increasing human population has not been fully realized. Plants, fungi, and animals harvested from forests have long provided multiple benefits—for nutrition, health, income, and cultural purposes. Across the globe, the main element of “fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 131 publications
0
19
0
1
Order By: Relevance
“…Direct provisioning of food from forests is not confined to the tropics, although quantifying relative contributions across countries globally is difficult because data on forest-sourced foods are generally not systematically collected. 30 However, a 2020 survey of households in 28 European countries found widespread local collection and consumption of forest plants and fungi, and indicated that the official data underestimated actual consumption by a factor of around ten. 31 In its 2020 Global Forest Resources Assessment, the Food and Agriculture Organization 32 asked countries to report on their ten most commercially important non-wood forest products, including food.…”
Section: Nutrient-rich Foodsmentioning
confidence: 99%
“…Direct provisioning of food from forests is not confined to the tropics, although quantifying relative contributions across countries globally is difficult because data on forest-sourced foods are generally not systematically collected. 30 However, a 2020 survey of households in 28 European countries found widespread local collection and consumption of forest plants and fungi, and indicated that the official data underestimated actual consumption by a factor of around ten. 31 In its 2020 Global Forest Resources Assessment, the Food and Agriculture Organization 32 asked countries to report on their ten most commercially important non-wood forest products, including food.…”
Section: Nutrient-rich Foodsmentioning
confidence: 99%
“…The global consumption of fruits is increasing due to the higher awareness of their health benefits and nutritional values 1 . Forests have an essential role in future food security as they represent a valuable source of vital nutrients and natural antioxidants 2 , 3 . Among fruits, berries have an enormous potential for the food industry as they are a rich source of bioactive compounds such as phenolic acids and anthocyanins 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Rừng đóng vai trò quan trọng trong việc cung cấp lương thực, đảm bảo dinh dưỡng, đem lại các giá trị bảo tồn văn hóa và thu nhập cho người dân trên toàn cầu (Temu và Msanga 1994;Härkönen và Vainio-Mattila 1998;Kajembe và cộng sự 2000;Ruffo và cộng sự 2002;Nyambo và cộng sự 2005;Caspersen và cộng sự 2018;Miller và cộng sự 2020;Chamberlain 2020). Các nghiên cứu trên toàn cầu đều chỉ ra rằng trên 30% dân số toàn cầu đang phụ thuộc trực tiếp vào nguồn lương thực từ rừng.…”
Section: Giá Trị Của Rừng Và Hệ Sinh Thái đếN Xã Hội Và Văn Hóaunclassified